2017
DOI: 10.1155/2017/6835813
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Complication of Multidrug Resistant Tuberculosis

Abstract: Introduction Capreomycin is a second-line drug often used for multidrug-resistant tuberculosis which can result in nephrotoxic effects similar to other aminoglycosides. We describe a case of capreomycin induced Bartter-like syndrome with hypocalcemic tetany. Case Report 23-year-old female patient presented with carpopedal spasms and tingling sensations in hands. Patient was being treated with capreomycin for two months for tuberculosis. On further investigation, hypocalcemia, hyponatremia, hypomagnesemia, hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…We also demonstrated lower serum magnesium levels in the 2 nd month of treatment in the capreomycin-based group; additionally, 2 subjects in this group had severe hypomagnesemia. To date, only case studies have reported hypocalcemia in patients treated with the capreomycin-based regimen and the kanamycin-based regimen [21, 25, 26]. In accordance with these previous case reports, our study revealed a decrease in ionized serum calcium in both groups, and this decrease was statistically significant within the capreomycin group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also demonstrated lower serum magnesium levels in the 2 nd month of treatment in the capreomycin-based group; additionally, 2 subjects in this group had severe hypomagnesemia. To date, only case studies have reported hypocalcemia in patients treated with the capreomycin-based regimen and the kanamycin-based regimen [21, 25, 26]. In accordance with these previous case reports, our study revealed a decrease in ionized serum calcium in both groups, and this decrease was statistically significant within the capreomycin group.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of severe hypokalemia was higher in the capreomycin-based group than in the kanamycin-based group. Two case reports by Holmes et al and Sharma and Sahay demonstrated hypomagnesemia in the MDR-TB patients who were treated with a capreomycin-based regimen [21, 25]. A study by Arnold et al found hypomagnesemia in some subjects within a capreomycin-based treatment group but found no evidence of hypomagnesemia in a kanamycin-based treatment group [24].…”
Section: Discussionmentioning
confidence: 99%
“…Management of drug-induced acquired Bartter's-like syndrome condition is to withhold the offending agent and correct the electrolyte imbalance. Drugs like indomethacin, potassium-sparing diuretics, and aldosterone receptor antagonists have been used [9]. In our patient, capreomycin was withheld and parenteral electrolyte correction was given initially followed by oral replacement for 6-8 weeks.…”
Section: Discussionmentioning
confidence: 92%
“…The literature search process is summarized in Figure 1 . For the final analysis, we evaluated 46 reports [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] published between 1961 and 2020 in English (N = 45) and Spanish (N = 1). They had been reported from the following countries: United States of America (N = 12), India (N = 8), United Kingdom (N = 7), Turkey (N = 4), Ireland (N = 3), Greece, Israel, Taiwan (N = 2), Australia, Belgium, Canada, Croatia, Paraguay, and Spain (N = 1).…”
Section: Resultsmentioning
confidence: 99%